Patient characteristics and procedural outcomes of moderate sedation for endoscopic procedures in patients with obesity: A retrospective, propensity score-matched study - Garg, Shashank; Syed, Shorabuddin; Perisetti, Abhilash; Inamdar, Sumant; Vargo, John (Endoscopy International Open, 2021)
Background Endoscopic procedures are performed commonly with moderate sedation. Obesity can pose a challenge in its safe administration. This study was aimed at assessing outcomes of endoscopy procedures performed with moderate sedation in obese patients.Patients and methods This was a retrospective study of patients undergoing esophagogastroduodenoscopy (EGD) and/or colonoscopy with moderate sedation from July 17, 2017 to December 31, 2019. Demographics, comorbidities, outpatient medications and procedure-related outcomes (procedure time, recovery time, cardiopulmonary adverse events, 7-day post-procedure hospitalization, cecal intubation time, withdrawal time, tolerance of moderate sedation and sedation medications administered) were compared for patient with and without obesity after propensity score matching. Standard statistical methods were used for analysis.Results A total of 7601 procedures were performed with moderate sedation for 5746 patients. Propensity score matching identified 1360 and 1740 pairs of EGDs and colonoscopies with moderate sedation for patients with and without obesity. Recovery time was found to be shorter for obese patients undergoing EGD (OR: 0.989, 95 % CI: 0.981–.998; P = 0.01). Obese patients did not differ from non-obese patients in any other procedure-related outcomes for EGDs or colonoscopies.Conclusions Outcomes for endoscopy procedures performed with moderate sedation were noted to be similar between obese and non-obese patients. These findings suggest that moderate sedation can be used safely for endoscopic procedures in patients with obesity.